Prevalence and factors associated with malnutrition among under 5-year-old children hospitalised in three public hospitals in South Africa - Makanda B. Itaka; Olufemi B. Omole (AOSIS, 2020)
Background: Malnutrition is a significant risk factor for ill health among children under 5 years of age and the consequences are significant. Aim: The aim of this study was to determine the prevalence and factors associated with malnutrition among under-5-year-old hospitalised children. Setting: This study was set at Sebokeng, Kopanong and Heidelberg hospitals, Sedibeng district, South Africa. Methods: This was a cross-sectional study comprising 306 hospitalised under-5-year-old children. Information on socio-demography, feeding practices, immunisation and clinical problems was obtained from caregivers and medical records. Anthropometric measurements were also performed. Results: Most participants were male (59.8%), had normal birth weights (80.0%), come from a household with a monthly income R2000 (about 150 US dollars) (50.3%), up-to-date immunisation (97.4%), breastfed for 6 months (57.4%) and were fed 3-4 meals/day (66.7%) and, at most, one snack/day (63.4%). Acute malnutrition accounted for 9.5% (n = 29) of admissions. Among these, 82.8% (n = 24) had severe acute malnutrition. On test of association, monthly household income (p = 0.01), mother's and father's employment status (p = 0.01; p = 0.01), breastfeeding history (p = 0.01) and having diarrhoea in index admission (p = 0.01) were significantly associated with malnutrition admission. In multivariate regression analyses, not being breastfed (odds ratio [OR] = 3.9; 95% confidence interval [CI]: 1.23-12.29; p = 0.02) and diarrhoea at index admission were independently associated with malnutrition (OR = 23.3; 95% CI: 6.85-79.43; p = 0.01). Conclusion: A significant proportion of participants had malnutrition and were subjected to suboptimal feeding practices. Healthcare providers in primary care need to entrench dietary education and anthropometric screening in all clinic visits for children 5 years old, particularly when they present with diarrhoea or are not being breastfed.